Filling the Vacancy of the Heirs: The Reasoning of the Supreme Court's Qiyās, Certainty of the Law of Adoption in Islamic Family Law - Dita Indriani Siregar; Muchlis Bahar; Elfia; Ahmad Syukran Baharuddin (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – This study critically evaluates the epistemological shift in Islamic inheritance law within contemporary Indonesian judicial practice by examining Supreme Court Decision No. 179 K/AG/1998 which employs qiyās (analogical reasoning) to grant a